Diagnostic of Cytokeratin-19 Gene Expression in Iranian Breast Cancer Patients : CK19 Gene Expression in Breast Cancer - Heidary Pour, Atefeh; Mansouri, Neda; Kolahi, Ali Asghar; Hassanian-Moghaddam, Hossein; Rezaei Tavirani, Mostafa; Mazloumi, Zeinab; Motallebi, Marzieh; Movafagh, Abolfazl; Iriti, Marcello; Aghamohammadi, Nicka (Cellular and Molecular Biology, 2022)
Sentinel lymph node (SLN) biopsy is currently the recommended procedure for axillary staging in clinically node-negative early breast cancer at diagnosis. The present study aimed to identify Cytokeratin-19 (CK19) gene profiles that accurately predicted the outcome of breast cancer patients. Fifty tumor samples from breast cancer patients were analyzed for the expression of the CK19 gene using quantitative PCR. Also, normal breast tissues (N = 50) were taken from the same patients that had undergone partial or total mastectomy. This gene signature was confirmed based on tumor’s stage, grade, and estrogen receptor (ER) status, using conditional logistic regression. Based on these findings, the negative reported lymph nodes for metastasis had micrometastasis in significant values. There was a significant difference between normal and cancer samples in CK19 expression. In this sentinel node evaluation, the relationship of this gene with tumor characteristics needs to be established and discussed finding a clear role for this gene in tumor outcome.